2017
DOI: 10.21272/jnep.9(4).04007
|View full text |Cite
|
Sign up to set email alerts
|

Impact of SWCNT Band Gaps on the Performance of a Ballistic Carbon Nanotube Field Effect Transistors (CNTFETs)

Abstract: Band gap is an important property in designing single-walled carbon nanotube (SWCNT) for nanoelectronic devices. This paper describes the impact of SWCNT band gaps on the performance of a ballistic carbon nanotube field effect transistor (CNTFET) using the 2D numerical simulator. The results demonstrate that with the reduction in SWCNT band gap the performance parameters such as transconductance, output conductance, Ion/Ioff current ratio, gain, and carrier injection velocity enhanced while the short channel e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
(13 reference statements)
1
7
0
Order By: Relevance
“…The results of the simulation presented thus far are in agreement with some of the studies conducted earlier on coaxial SW-CNTFETs with SiO 2 as the gate dielectric [7,8,13].…”
Section: Trans-conductance (G M ) Output Conductance (G D ) Gainsupporting
confidence: 88%
See 1 more Smart Citation
“…The results of the simulation presented thus far are in agreement with some of the studies conducted earlier on coaxial SW-CNTFETs with SiO 2 as the gate dielectric [7,8,13].…”
Section: Trans-conductance (G M ) Output Conductance (G D ) Gainsupporting
confidence: 88%
“…In the past, researchers have demonstrated the scaling effects of gate insulator thickness on the performance of CNTFETs. It was shown that an increase in SiO 2 insulator thickness causes a decrease in drive current along with the strengthening of the short channel effects for a CNT with diameter 3nm, a threshold voltage of 0.4V, gate control of one and drains control equal to zero [7]. If the oxide thickness is reduced from 5nm to 1.5nm there is an increase in threshold voltage and the subthreshold swing remains close to its theoretical limit of 60mV/dec [8].…”
Section: Introductionmentioning
confidence: 96%
“…Among of those high-k gate insulators, BZN thin films have shown the best performance due to the formation of the partial nanocrystalline BZN phase in the amorphous matrix [14]. The use of BZN film as a gate insulator for ZnO-TFTs have been reported by Kim et al, the on/off current ratio of 2.4 × 10 4 and threshold voltage of 2 V had been obtained [15]. Effect of gate insulator on performance of carbon nanotube field effect transistors was reported by Dass [16].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we have discussed the various simulation results [7] we have study the influence of chirality and gate insulator thikness on (I-V) characteristics of CNTFET, and observes the parameter changing eflect on it. Besides, further analysis has been done through the comparison of' the other group to justify result.…”
Section:  Issn: 2088-8708mentioning
confidence: 99%
“…The positive velocity states N 1 are occupied by the source and the negative velocity states N 2 are occupied by the drain. N 1 and N 2 and are given by [24]:…”
Section: Cntfets Simulation Modelmentioning
confidence: 99%